A qualitative study exploring tactical performance determinants from the perspective of three Rugby World Cup coaches. Issue 4 (August 2022) - Colomer, Carmen M. E.; Pyne, David B.; Mooney, Mitch; McKune, Andrew; Serpell, Benjamin G.
Experiential knowledge of elite international coaches was investigated to reveal insights on successful rugby union strategies and tactics required to prevail in international competition. Three elite coaches who coached at a Rugby World Cup were interviewed using an in-depth, semi-structured approach. They were asked about specific strategies and tactics which they believed were required to be successful in an upcoming international tournament and a thematic analysis of qualitative data followed. Particular interest was paid to the influence of potential constraints and how these factors impact performance behaviours over time. The importance of an effective tactical kicking game in attacking strategies was highlighted, along with an adaptable defensive structure following a turnover. Unsuccessful performance behaviours in international rugby were reported to be connected with an irrational kicking game, a weak defensive line and losing possession off set-piece plays. These results support the need for a multidisciplinary approach, where exploring coaches' knowledge presents an opportunity to enhance understanding across the performance analysis field. Further research is needed to complement experiential knowledge with quantitative research in rugby performance analysis.